Thermal Properties of Cotton Fabric Coated with Polypyrrole (Journal of Fiber Bioengineering and Informatics, 2012)
Polypyrrole was chemically synthesized by in situ polymerization in the presence of surfactant dopant oncotton denim fabric. Shape and size of the particles are characterized by SEM micrographs. Electricaland thermal conductivity of fabric samples were measured and it was found that electrical conductivitycan be increased by increasing the concentration of polypyrrole, but there is no significant relationbetween electrical and thermal conductivities.
Keywords: Polypyrrole; Cotton Fabric; Thermal Conductivity